Let the present age of the daughter be x years. Four years ago, the age of the daughter = (x - 4) years Four years ago, the age of the mother = 12 × (x - 4) = (12x - 48) years Two years hence, Age of the daughter = (x - 4) + 4 + 2 = (x + 2) years Age of the mother = (12x - 48) + 4 + 2 = (12x - 42) years According to the question, (x + 2) × 4 = (12x - 42) =4x + 8 = 12x - 42 = 12x – 4x = 42 + 8 8x =50 x = 6.25 Now, the present age of the mother = (12x - 48) + 4 = 12x - 44 = 12 × 6.25 - 44 = 31 Let after y years the age of the mother will be three times that of her daughter. According to the question, (6.25 + y) × 3 = (31 + y) = 18.75 + 3y = 31 + y = 2y = 31 – 18.75 y = 12.25/2 y = 6.125=6(1/8) years. After 6(1/8) years, the mother's age will be 3 times that of her daughter.
Materia Medica, one of the earliest books on botanical studies was written by
Instrument used for measuring Relative humidity accurately in the crop canopy:
Minimum Support Price is announced for how many crops?
What is the term for the complete set of activities involved in the timber harvesting process, including cutting down trees, removing branches, cutting ...
‘Parawilt’ of cotton is:
What type of epistasis occurs when recessive alleles at one locus mask the expression of both dominant and recessive alleles at another locus?
White tail disease in freshwater prawn is caused by
Minimum germination limits prescribed for labelled seed of cotton is
Which one of the following is not the principles of Farm Finance?
Who used the term 'organic farming' for the first time?